Why fiscal and Phillips Curve theories of inflation are not working - GREENWOOD, John (Journal of Economics Bibliography, 2026)
During the 2016-17 bull market in the US investors have been subjected to two main market scares – the possibility of near term inflation and the threat of an imminent recession, both spelling the end of the business cycle expansion. This paper examines first two commonly cited theories of inflation: the fiscal theory of the price level, and the Phillips curve (or output gap). Each is a form of reduced form analysis that omits any reference to the underlying monetary causes of inflation. I show that both in the US and more broadly across the OECD money and credit growth remain subdued. Since inflation is ultimately a monetary phenomenon, no sharp upswing in inflation can occur without a sustained period of faster money and credit growth. Second, the paper reviews briefly the basis for an extended business cycle expansion. The shape of the yield curve, money growth and the health of private sector balance sheets imply there is currently no basis for predicting an imminent recession. This justifies the view that the current expansion will continue for several more years with low inflation. Keywords. Fiscal theory of the price level; Phillips curve; Inflation; Monetary growth. JEL. E62; H54; O40.